Pediatric Outpatient/Urgent-Care Emergency and Disaster Planning. Issue Volume 34:Issue s1(2019) (May 2019) - Frogel, Michael; Foltin, George; Cooper, Arthur
Abstract : Introduction: Children are frequently victims of disasters, however important gaps remain in pediatric disaster planning. This includes a lack of resources for pediatric preparedness planning for patients in outpatient/urgent-care facilities. The New York City Pediatric Disaster Coalition (NYCPDC) is funded by the NYC Department of Health and Mental Hygiene (DOHMH) to improve NYC's pediatric disaster preparedness and response. Aim: After creating planning resources in Pediatric Long-Term Care Facilities, Hospital Pediatric Departments, Pediatric and Neonatal Intensive Care Units and Obstetric/Newborn Services within NYC hospitals, the NYCPDC partnered with leaders and experts from outpatient/urgent-care facilities caring for pediatric patients and created the Pediatric Outpatient Disaster Planning Committee (PODPC). PODPC's goal was to create guidelines and templates for use in disaster planning for pediatric patients at outpatient/urgent-care facilities. Methods: The PODPC includes physicians, nurses, administrators, and emergency planning experts who have experience working with outpatient facilities. There were 21 committee members from eight organizations (the NYCPDC, DOHMH, Community Healthcare Association of NY State, NY State DOH, NYC Health and Hospitals, Maimonides Medical Center and Presbyterian/Columbia University Medical Center). The committee met six times over a four-month period and shared information to create disaster planning tools that meet the specific pediatric challenges in the outpatient setting. Results: Utilizing an iterative process including literature review, participant presentations, discussions review, and improvement of working documents, the final guidelines and templates for surge and evacuation of pediatric patients in outpatient/urgent care facilities were created in February 2018. Subsequently, model plans were completed and implemented at five NYC outpatient/urgent-care facilities. Discussion: An expert committee utilizing an iterative process successfully created disaster guidelines and templates for pediatric outpatient/urgent care facilities. They addressed the importance of matching the special needs of children to available space, staff, and equipment needs and created model plans for site-specific use.